Space chronicles : facing the ultimate frontier - Tyson, Neil deGrasse (W.W. Norton, 2012)
Astrophysicist Neil deGrasse Tyson presents his views on the future of space travel and America's role in that future, giving his readers an eye-opening manifesto on the importance of space exploration for America's economy, security, and morale.